Triolein emulsion enhances temozolomide brain delivery: an experimental study in rats. (1st January 2021) - Seung, Won-Bae; Cha, Seung Heon; Kim, Hak Jin; Choi, Seon Hee; Lee, Juho; Kwak, Dongmin; Kim, Hyunwoo; Yoo, Jin-Wook; Kim, Yong-Woo; Kim, Sang Kyoon; Lee, Da-Sol
Abstract: Purpose: To evaluate the enhancement of temozolomide (TMZ) delivery in the rat brain using a triolein emulsion. Materials and Methods: Rats were divided into the five groups as following: group 1 (negative control), group 2 (treated with triolein emulsion and TMZ 20 mg/kg), and group 3 (TMZ 20 mg/kg treatment without triolein), group 4 (treated with triolein emulsion and TMZ 10 mg/kg), and group 5 (TMZ 10 mg/kg treatment without triolein). Triolein emulsion was infused into the right common carotid artery. One hour later, the TMZ concentration was evaluated quantitatively and qualitatively using high-performance liquid chromatography (HPLC-MS) and desorption electrospray ionization mass spectrometry (DESI-MS) imaging, respectively. The concentration ratios of the ipsilateral to contralateral hemisphere in each group were determined and the statistical analysis was conducted using an unpaired t -test. Results: Quantitatively, the TMZ concentration ratio of the ipsilateral to the control hemisphere was 2.41 and 1.13 in groups 2 and 3, and were 2.49 and 1.14 in groups 4 and 5, respectively. Thus, the TMZ signal intensities of TMZ in group 2 and 4 were statistically high in the ipsilateral hemispheres. Qualitatively, the signal intensity of TMZ was remarkably high in the ipsilateral hemisphere in group 2 and 4. Conclusions: The triolein emulsion efficiently opened the blood-brain barrier and could provide a potential new strategy to enhance the therapeutic effect of TMZ. HPLC-MS and DESI-MS imaging were shown to be suitable for analyses of enhancement of brain TMZ concentrations.